Revisiting surgical management of breast cancer in a geriatric population - Kesicioglu,Tugrul (2022)
Abstract OBJECTIVE: Breast cancer is a leading cause of death not only in the young population but also in the elderly. There are no consensus treatment guidelines for elderly breast cancer patients. We purposed to discuss surgical treatment options for breast cancer cases over 80 years concerning morbidity and mortality. METHODS: This retrospective study includes 58 patients over 80 years of age at the time of surgery for breast cancer between 2006 and 2017. A sum of 58 cases (54 females and 4 males), over 80 years of age, with an average age of 84.5±4.07 (80–94) years were included in the study. The modified radical mastectomy was the most common surgical modality in 30 (51.7%) cases, and the axillary intervention was performed on 41 (70.7%). Axillary dissection and sentinel lymph node biopsy were performed for 30 (51.7%) and 11 (18.9%) cases, respectively. RESULTS: Minor and major complications were observed in 8 (13.8%) cases. The average follow-up period of the patients was 37.5 (1–120) months. During the follow-up period, breast cancer-related mortality was observed in 9 (15.52%) cases. No statistical differences were detected in mortality with/without axillary intervention and chosen surgical modality. CONCLUSIONS: Comorbidity, the American Society of Anesthesiologists score, and life expectancy should be considered in the management and surgical planning of patients over 80 years of age with breast cancer. Minimally invasive approaches should be preferred for the elderly whenever feasible and applicable in the light of oncologic surgery principles in order to reduce complications and mortality rates.